Enhanced damage resistance and novel defect structure of CrFeCoNi under in situ electron irradiation. (December 2016) - He, Mo-Rigen; Wang, Shuai; Jin, Ke; Bei, Hongbin; Yasuda, Kazuhiro; Matsumura, Syo; Higashida, Kenji; Robertson, Ian M.
Abstract: Defect production and growth in CrFeCoNi, a single-phase concentrated solid solution alloy, is characterized using in situ electron irradiation inside a transmission electron microscope operated at 400–1250 kV and 400 °C. All observed defects are interstitial-type, either elliptical Frank loops or polygonal (mostly rhombus) perfect loops. Both forms of loops in CrFeCoNi exhibit a sublinear power law of growth that is > 40 times slower than the linear defect growth in pure Ni. This result shows how compositional complexity impacts the production of Frenkel pairs and the agglomeration of interstitials into loops, and, thus, enhances the radiation tolerance. Graphical abstract: